Brain‐Targeted HFn‐Cu‐REGO Nanoplatform for Site‐Specific Delivery and Manipulation of Autophagy and Cuproptosis in Glioblastoma. Issue 2 (18th November 2022) - Jia, Wenhui; Tian, Hailong; Jiang, Jingwen; Zhou, Li; Li, Lei; Luo, Maochao; Ding, Ning; Nice, Edouard C.; Huang, Canhua; Zhang, Haiyuan
Abstract: Durable glioblastoma multiforme (GBM) management requires long‐term chemotherapy after surgery to eliminate remaining cancerous tissues. Among chemotherapeutics, temozolomide is considered as the first‐line drug for GBM therapy, but the treatment outcome is not satisfactory. Notably, regorafenib, an oral multi‐kinase inhibitor, has been reported to exert a markedly superior effect on GBM suppression compared with temozolomide. However, poor site‐specific delivery and bioavailability significantly restrict the efficient permeability of regorafenib to brain lesions and compromise its treatment efficacy. Therefore, human H‐ferritin (HFn), regorafenib, and Cu 2+ are rationally designed as a brain‐targeted nanoplatform (HFn‐Cu‐REGO NPs), fulfilling the task of site‐specific delivery and manipulating autophagy and cuproptosis against GBM. Herein, HFn affords a preferential accumulation capacity to GBM due to transferrin receptor 1 (TfR1)‐mediated active targeting and pH‐responsive delivery behavior. Moreover, regorafenib can inhibit autophagosome‐lysosome fusion, resulting in lethal autophagy arrest in GBM cells. Furthermore, Cu 2+ not only facilitates the encapsulation of regorafenib to HFn through coordination interaction but also disturbs copper homeostasis for triggering cuproptosis, resulting in a synergistical effect with regorafenib‐mediated lethal autophagy arrest against GBM. Therefore, this work may broaden the clinical application scope of Cu 2+ and regorafenib in GBM treatment via modulating autophagy and cuproptosis. Abstract : Human H‐ferritin (HFn), regorafenib, and Cu 2+ are rationally designed as a brain‐targeted nanoplatform, fulfilling the task of site‐specific drug delivery and manipulating autophagy and cuproptosis against glioblastoma. Cu 2+ not only facilitates the encapsulation of regorafenib to HFn through coordination interaction but also disturbs copper homeostasis for triggering cuproptosis, resulting in a synergistic effect with regorafenib‐mediated lethal autophagy arrest against glioblastoma.